Copper-alumina nanocomposite coating on copper substrate through solution combustion. Issue 3 (15th February 2018) - Mohammadi, E.; Nasiri, H.; Khaki, J. Vahdati; Zebarjad, S.M.
Abstract: The main objective of the present research is to investigate the production of Cu-Al2 O3 nanocomposite coating on a copper substrate using solution combustion synthesis. Solution combustion synthesis is mainly used to produce nanocomposite powders; however, in this study it is applied to produce nanocomposite coat. For this purpose, both copper and aluminum nitrates (Cu (NO3 )2 ·3H2 O and Al (NO3 )3 ·9H2 O) are used as oxidizers. Also, urea and graphite are respectively used as fuel to synthesize the Cu-Al2 O3 nanocomposite and as inhibitor to prevent the oxidation of the synthesized copper. The microstructure and morphology of the nanocomposite coating, which includes 25 wt% alumina as the reinforcing phase, was studied using X-ray diffraction, scanning electron microscopy, and transmission electron microscopy at different fuel/oxidizer ratios ranging from 0.9 to 2. The temperature variation during the process was measured as a function of time using a precise thermocouple. Finally, micro-hardness and wear tests were conducted on the nanocomposite coating. The results verified the formation of Cu-Al2 O3 nanocomposite coating. Time-temperature curve illustrated that the highest temperature was achieved at the fuel/oxidizer ratio of 1.25. The results of the microhardness and wear resistance test showed that these properties depend heavily on the fuel/oxidizer ratio, with the best condition attained at the ratio of 1.25.